Risiko Kesehatan Lingkungan dan Gangguan Pernapasan pada Masyarakat yang Tinggal di Sekitar Kawasan Industri di Kota Makassar, Indonesia - Yulistiani, Liana; Pratama, Ananda (Journal of Applied Health Sciences, 2026)
Industrial growth in Makassar City has expanded in parallel with increasing urban economic activities. This development occurs alongside densely populated residential areas and poses significant environmental health risks, particularly respiratory disorders. Continuous exposure to industrial air pollutants may adversely affect community health. This study aims to analyze the relationship between environmental health risks and the occurrence of respiratory disorders among communities living around industrial areas in Makassar City, Indonesia. This study employed an analytical observational design with a cross-sectional approach. A total of 200 adult respondents who had resided for at least five years in areas surrounding industrial zones were included. Data were collected using structured questionnaires and environmental observation checklists. The independent variable was environmental health risk, measured through ambient air quality, distance of residences from industrial areas, and physical housing conditions. The dependent variable was respiratory disorders, assessed based on reported respiratory symptoms within the last six months. Data analysis was conducted using univariate and bivariate statistical methods. The results showed that 59.0 percent of respondents experienced respiratory disorders. Most respondents were exposed to moderate to high levels of environmental health risk. Bivariate analysis indicated a significant association between environmental health risk and respiratory disorders, with a p-value of 0.001. Respondents living within less than one kilometer from industrial areas had a higher prevalence of respiratory disorders compared to those residing farther away. The discussion highlights that industrial environmental exposure plays a dominant role in increasing the risk of respiratory disorders. Long-term exposure and close residential proximity to pollution sources intensify adverse health effects. Environmental factors were found to have a stronger influence than individual factors. This study concludes that effective control of industrial pollution and healthy spatial planning are essential to protect community health in industrial areas of Makassar City. The findings provide empirical evidence to support evidence-based environmental health policies at the local level.